REVISITING ALVARADO SCORE FOR NEGATIVE APPENDICECTOMY RATE AT AYUB TEACHING HOSPITAL ABBOTTABAD - Haider Kamran,; Akbar, Ismail; Amjad Farooq,; Zulfiqar Ali,; Zainab Ali,; Shawana Asad,; Faiza Dawood Khan,; Tayyeba Hassan, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Surgeons specifically junior ones in our setup of third world country face the issue of diagnosing Acute Appendicitis (AA) as presentation usually is not typical. Cases presenting at odd hours may put residents & house officers in trouble, when sophisticated investigations are either un-available or expansive. Need for a structured diagnostic criterion is thus always there. Various scores have been designed to help out surgeon e.g. Alvarado score which got more popular & is practiced randomly. Aim of this study was to revisit Alvarado score for its efficacy in current era at Ayub Teaching Hospital (ATH) Abbottabad, i.e., by calculating negative appendicectomy rate. Methods: This descriptive study was conducted at Surgical B Unit (ATH) from 1st September 2021 to 31st May 2022. 160 patients with pain RIF were included & evaluated by Alvarado score & consequently placed in 03 groups. Those having score 1-4 (Group-1) at presentation were discharged while the ones with score 5-6 (Group-2) were observed, re-evaluated at interval for re-grouping as Group-1 or 3 based on their final score. Patients with score 7-10 (Group-3), having score confirmed Acute Appendicitis were operated. Findings were recorded on a proforma. SPSS-version 26 was utilized for statistical analysis. Results: Total patients were 160, males were 118 & female patients were 42. Discharged (Group-1) patients were 22. Group-2 patients (41 in number), were observed for 24-48 hour when score of 16 declined to ‰¤4 level & were discharged. 25 patients whose score increased to ‰¥7 level were operated like other 97 patients of Group-3. Histopathology confirmed 109 of 122 patients as acute appendicitis while 13 turned out negative appendicectomies. Negative appendicectomy rate was therefore 10.65% i.e. 13 out of 122, it was 06.17% in males (i.e., 05 of 81) & 19.51% (i.e., 08 of 41) in females. Conclusion: Alvarado score again proved helpful even today in reducing the negative appendicectomy rate at surgery department of ATH, it should therefore be routinely adopted in diagnosis of suspected appendicitis cases in the third world countries (e.g. Pakistan) setup (facing scarcity of sophisticated resources).